A simple method for discrimination of carcinomatous meningitis using CEA, total protein, and total cell count in the cerebrospinal fluid of primary lung cancer patients. Issue 14 (9th April 2021) - Ogawa, Yukari; Saraya, Takeshi; Noda, Akinari; Kurokawa, Nozomi; Sakuma, Sho; Aso, Kaori; Mikura, Sunao; Oda, Miku; Ishida, Manabu; Honda, Kojiro; Nakamoto, Keitaro; Tamura, Masaki; et al.
Abstract : Abstract: Carcinomatous meningitis (CM) is a critical issue for physicians. However, no study has reported a simple and useful diagnostic or predictive marker for CM. This study aimed to elucidate the potential markers for diagnosing CM derived from cerebrospinal fluid (CSF). We retrospectively enrolled 78 lung cancer patients with suspected CM during the clinical course, including 42 CM and 36 non-CM patients. We compared the clinical and CSF findings, including carcinoembryonic antigen (CEA), between CM and non-CM patients, and explored the diagnostic markers for early identification of CM as well as the contributing factors for mortality. On CSF analysis, with cutoff values of CEA ≥5 ng/ml, total protein (TP) in CSF ≥45 g/dl, and total cell count (TCC) ≥7 cells/μL, the sensitivity, specificity, and area under the curve (AUC) for CM were 85.7%, 84.6%, and 0.887 (95% CI: 0.758–1.0, P  < .001); 80.5%, 69.4%, and 0.755 (95% CI: 0.646–0.865, P  < .001); and 56.1%, 100%, and 0.817 (95% CI: 0.722–0.912, P  < .001), respectively. TP levels in CSF ≥the patients' age had a sensitivity, specificity, and an AUC of 48.8%, 77.8%, and 0.633 (95% CI: 0.722–0.912, P  = .045) for CM, respectively. Among CM patients, patients with 'TP in CSF (>patients' age)" (n = 19, P  = .008) showed significantly shorter 90-day survival probability than the residual patients (n = 20). None of the CSF parameters could predict the risk of mortality on Cox regression analysis. The cutoff value of CEA ≥5 ng/ml in CSF is a simple and useful method with a high diagnostic value for CM diagnosis, but not a suitable predicting factor for mortality. 'TP in CSF >patients' age" might be a novel factor for assessing short-term mortality.